Seasonality and movement patterns of butterflies in an intermediate zone regenerating forest habitat in Sri Lanka - Buddhika Weerakoon (International Academy of Ecology and Environmental Sciences, 2021)
The seasonality of butterflies in the intermediate zone of Sri Lanka was assessed by monitoring the abundance, diversity and occurrence of butterflies in Maragamuwa Forest Regeneration Study Site (FRSS), which consists of two forest types: moderately mature forest of 30 years age (refers as Late Secondary Forest-LSF) and much younger forest of 10 years old (refers as Early Secondary Forest-ESF). The highest butterfly abundance in FRSS was recorded in October to December followed by April to June. In ESF butterfly abundance and species richness were high in October to December (n=26) followed by March and April (n=25) which are the rainy seasons. But in LSF butterfly abundance and richness were high in May and June (n=43), which is the dry season. Most of butterflies recorded throughout the year, while some species recorded only in wet season. Two butterfly migratory seasons were identified in October and March. Appias galane and Catopsilia pomona were the main species migrate in October and Appias albino and Cepora nerissa migrated in March. The study had concluded that butterfly seasonality was associated with the climate; and the local movement of butterflies within adjoining forest habitats had caused the temporal variation of the community.